(untitled) (European Journal of Health Research, 2019)
Life expectancy is increasing in first world societies so it is a priority to ensure a satisfactory and healthy life throughout life until the end of it. Furthermore, we know that depression is one of the mental illnesses that most prevails in the elderly. In the actual study, we worked with the students of the first year of the University of the Basque Country, all of them studying in the Experience Classrooms of Biscay. We evaluate the presence of depressive symptomatology, as well as its relationships with other people in order to see if attending to those classes is related with an improvement in depression and to analyze relationships between different psychological and relational variables. Our results suggest that the University for over 55 years old can improve the symptomatology of depression and that this improvement is related to other psychological and relational variables. We underline the importance to continue creating resources for the elderly people in order to help prevent isolation, mental health problems and promote well-being.